Testing the Efficiency of The Sawdust dan Wood Glue Particulate Filters to Reduce The PM2.5 Emissions from Motorcycles - Arinto Yudi Ponco Wardoyo; Arsyal Karismadika Rumpoko; Abdurrouf Abdurrouf (Natural B, Journal of Health and Environmental Sciences, 2018)
The increase of motor vehicle population in Indonesia causes the increase of pollution substances in ambient air, such as Particulate Matter with the diameter <2.5 µm or fine particle (PM2.5). There are many methods developed to reduce the PM2.5 concentrations emitted by motor vehicles, such as a biomass particulate filter. This study was aimed to develop biomass PM2.5 filters made of sawdust and wood glue with three different composition ratio: F1, F2, and F3. The PM2.5 concentrations before and after passing through the filters were measured using a Digital Dust Monitor (Kanomax, Model 3443) for 200 seconds of the sampling times. The filter efficiency was obtained from the reduction ratio of the PM2.5 concentrations before and after being filtered. Based on the surface morphology test using an electron microscope SEM, the diameters of the filter pores were 9.11 – 19.7 µm with the different densities. The efficiency was 33% to 52%, depending on the ratio of the sawdust and wood glue. A higher filter density (2.72 x 10-3 g/cm3) generated a higher filter efficiency (52%).